Implementasi Hue Saturation Value (HSV) Untuk Identifikasi Fraktur Tulang - Rita Zahara (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Fracture or fracture is a break in the continuity of the bone, most of the fractures occur as a result of trauma, some fractures occur secondary to a disease process such as osteoporosis which causes pathological fractures. The cause of fracture is trauma, which is divided into direct trauma, indirect trauma, and minor trauma. The problem in this research is that the system can be designed to work properly to perform image processing which has shortcomings in the advantages of detection of edge images on bone invoices. Hue is a color known to humans such as red and green, colors that are captured by the human eye based on the wavelength produced. Saturation represents the purity level of the color or the amount of white light mixed with the hue. Each pure color has a saturation value of 100%. Edge detection serves to identify the outline of an object against an overlapping background. Color segmentation is the separation of segments in an image based on the colors contained in the image.